Tact Emergence and Speech Accuracy by Multiple Exemplar Instruction in Children With Little Verbal Repertoire - de Souza Mascotti, Thais [UNESP]; Almeida Verdu, Ana Claudia Moreira [UNESP]; Silva, Leandra Tabanez Nascimento; LaFrance, Danielle; McIlvane, William J. (Universidad de Guadalajara, 2024)
The inductive role of Multiple Exemplar Instruction (MEI) in the emergence and integration of listener and speaker operants is of scientific and social interest. This study verified whether the emergence of tacts after listening training would be induced by MEI in four children who did not emit tacts initially. Three participants with diagnoses of autism spectrum disorder, two boys, and one girl at six to eight years old. One participant was diagnosed with hard of hearing and used a cochlear implant. The participants were evaluated VB-MAPP scored Level 1 in tact, and had different diagnoses. The procedure was carried out in phases. The pre-test assessed the listener, echoic, and tact and selected three sets of stimuli for the next phases. Listener training and tact test demonstrated functional independence between the operants (set 1). The MEI taught the operants of listener, echoic, and tact (set 2). Repeating the listener training and tact test verified the inductive potential of the MEI on the emergence of tact (set 1). Listener training and tact testing verified the effects of MEI with a new set of stimuli (set 3). The three post-tests and three followups evaluated maintenance (three sets). The echoic behavior was systematically monitored during testing. Before MEI listener training was not a condition for the emergence of tact; the percentage of correct responses in tact was very low or null for all participants. After MEI (set 2) there was an increase in the percentage of correct in three operants and tact emergence after listener training for set 1 and set 3 (new set). The variability was persistent but all measures in post-tests and follow-ups were at a level above the major level of baseline. The speech accuracy is better in the post-test than pretest. Except for one participant (Julie) the error type no response or complex errors decreased and correct answers or simple errors increased. The MEI components and number of exposures required are variables that must be investigated in the tact emergency.
Emergência de Tato e Precisão da Fala via Instrução por Múltiplos Exemplares em Crianças com Pouco Repertório Verbal
Keywords: Multiple-Example Instruction; speech accuracy; tact